“I feel like people would look at me like I’m dirty or like I’m a thief:” a qualitative exploration of interpersonal and intrapersonal experiences that influence recovery among adults at risk of opioid-related overdose - Szlyk, Hannah S.; Jones, Sara; Michener, Jordan; Zhang, Zhuoran; Kaiser, Nina; Holtz, Heidi; Frempong, Melody Rachel Konadu; Lateef, Husain; Hutson, William; Cavazos-Rehg, Patricia (Frontiers in Public Health, 2025)
ObjectiveDue to the nature of early termination of treatment and the transient lifestyles of many people who use substances, many providers are unaware of the factors that may have contributed to their client’s engagement in treatment. Treatment providers and researchers need a better understanding of intrapersonal and interpersonal factors that impact recovery from the clients’ perspective. This study uses qualitative methods to explore these factors.MethodsEligible participants were adults who had used opioids and/or stimulants and were receiving treatment at a consenting facility. Participants completed one-month follow-up interviews after using a mobile health intervention. Transcripts were analyzed using deductive thematic analyses. Two research staff members coded the transcripts independently. The third coder identified coding discrepancies.ResultsOut of 24 participants, most were middle-aged, and the majority identified as female and as white. Half of participants (n = 12) shared that they have recovery-related worries, predominantly about finances and finding work after treatment. Twenty participants (n = 20) discussed how they currently take care of their daily needs. All participants shared proactive factors that support recovery, specifically seeking motivation from loved ones. Conversely, many participants shared how they had strained familial relationships when using substances. Twenty participants reported experiencing the theme of stigma due to their substance use, specifically by family members and providers.ConclusionMost participants are concerned about their financial future; the respective treatment facilities help to meet current basic needs. Most participants have relationships with family members and identify them as a source of support in recovery. Overall, many individuals in recovery have the tools to address interpersonal and intrapersonal challenges. Patients may still benefit from assistance planning for life post-treatment.